Modification of Penjasorkes Learning at the Integrated Islamic Elementary School Adzkia 1 Padang - Alfroki Martha; Alfiyandri Alfiyandri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This study describes the Modification of Physical Education and Health Learning at SDIT Adzkia 1 Padang. This study aims to integrate learning between physical education and health (Penjasorkes). These modifications are limited to Tools and Rules. This type of research is descriptive quantitative, in which this research looks at the percentage of ratings from the research analysis. The population and sample in this study were all 256 students of SDIT Adzkia 1 Padang. The sampling technique used is Purposive Sampling, namely there are certain considerations, therefore the selected sample is 20 people. The research instrument used a research questionnaire using a Likert Scale. The results of data processing from Modification of tools with a high percentage are Alternative answers 5 (Strongly agree) with a total percentage of 49.95%. Based on these results, the Modification of Physical Education Learning at SDIT Adzkia 1 Padang is in the Enough category. Then, the results of data processing from Modification of Regulations in Alternative answer 5 (Strongly agree) with a total percentage of 49%. Based on these results, the Modification of Physical Education Learning at SDIT Adzkia 1 Padang is also in the Enough category.